The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0100-69912007000100010
|View full text |Cite
|
Sign up to set email alerts
|

Alterações morfométricas da musculatura dos músculos longitudinal e circular de ratos submetidos à criação de piloros no intestino delgado

Abstract: OBJETIVO: Realizar um estudo morfométrico comparativo da musculatura longitudinal e circular do intestino delgado de ratos submetidos à construção cirúrgica de um e de dois piloros no intestino delgado utilizando-se da técnica de criação de piloros proposta por Rena et al. MÉTODO: Foram utilizados 52 ratos Wistar machos divididos em três grupos. O Grupo A, destacado como controle, composto de 10 animas, cada um forneceu 20mm de segmento de intestino para o estudo. Os animais do Grupo B, composto de 32 animais,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…The seromyotomy undertaken in the valve construction results in local denervation [4][5][6]13 . In this denervated segment, there To extrapolate the current findings to human beings, we conclude with future perspectives of more studies that consider the systematic analysis of other elements, such as interstitial cells of Cajal, neurotransmitters and the physiology of the operated segment, submucosal plexus of Meissner and colonic mucosa 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The seromyotomy undertaken in the valve construction results in local denervation [4][5][6]13 . In this denervated segment, there To extrapolate the current findings to human beings, we conclude with future perspectives of more studies that consider the systematic analysis of other elements, such as interstitial cells of Cajal, neurotransmitters and the physiology of the operated segment, submucosal plexus of Meissner and colonic mucosa 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The creation of sphincter mechanisms in the small intestine is related to the control of intestinal transit speed, particularly in bowel resections. Studies in rats, dogs and humans has shown that artificial valves slow intestinal transit and promote weight gain after intestinal resections 18,[23][24][25][26] . Besides these results, some described techniques show reduction of colonization of the proximal segments of the small intestine through the identification of bacterial growth by intraluminal collections or stool culture.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Publicações anteriores evidenciaram a capacidade dessas válvulas de retardarem o trânsito intestinal, sem ocasionar obstrução. Desconhecemse, no entanto, suas interferências na adaptação intestinal [6][7][8][9] . O presente trabalho visa avaliar as alterações morfométricas das vilosidades intestinais de ratos submetidos à criação cirúrgica dessas válvulas.…”
Section: Furtado Et Alunclassified
“…Em 2007, Rena et al publicaram o estudo da morfometria das camadas longitudinal e circular do intestino dos animais que constituíram o Grupo V do presente trabalho. O aumento da camada muscular, em comparação com o controle, não ultrapassou 2,09 vezes no músculo circular e 2,34 vezes no longitudinal 8 . Uma estenose cirúrgica levou ao aumento superior a dez vezes na camada muscular do intestino de animais 46 .…”
Section: Furtado Et Alunclassified